2021
DOI: 10.1108/ecam-12-2020-1048
|View full text |Cite
|
Sign up to set email alerts
|

The mediating role of job stress on the relationship between job satisfaction facets and turnover intention of the construction professionals

Abstract: PurposeThe present study examines the mediating role of job stress on the relationship between job satisfaction facets and turnover intention of the construction project professionals in Sri Lanka.Design/methodology/approachData were gathered from a cross-sectional survey of 274 project-level employees of 10 construction organizations in Sri Lanka. A path analytical model is developed to assess the research hypotheses.FindingsResults support the mediation model of job stress, in which satisfaction with supervi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 52 publications
(48 citation statements)
references
References 60 publications
(108 reference statements)
1
47
0
Order By: Relevance
“…Some of these detrimental effects are empirically validated in the construction literature itself. Dodanwala and Santoso (2021) evaluated the link between job satisfaction facets, job stress, and turnover intentions of construction project professionals in Sri Lanka and concluded that job stress is the most significant variable predicting construction employees' turnover intentions. Besides, studies of Leung, Chan and Olomolaiye (2008), Leung, Yee andDongyu (2011), andLeung, Liang andChan (2017) assessed how workplace stress influences the performance of construction project managers and other construction professionals.…”
Section: Literature Review Job Stressmentioning
confidence: 99%
See 4 more Smart Citations
“…Some of these detrimental effects are empirically validated in the construction literature itself. Dodanwala and Santoso (2021) evaluated the link between job satisfaction facets, job stress, and turnover intentions of construction project professionals in Sri Lanka and concluded that job stress is the most significant variable predicting construction employees' turnover intentions. Besides, studies of Leung, Chan and Olomolaiye (2008), Leung, Yee andDongyu (2011), andLeung, Liang andChan (2017) assessed how workplace stress influences the performance of construction project managers and other construction professionals.…”
Section: Literature Review Job Stressmentioning
confidence: 99%
“…Age is a conspicuous variable in stress-related studies as prior research has demonstrated that age links to employees' job attitudes and well-being. The literature mainly suggests that older employees tend to report better well-being and more favorable workplace views than younger ones (Ng and Feldman, 2009;Boyas, Wind and Kang, 2012;Dodanwala and Santoso, 2021). This is because younger employees are at a higher risk for adverse outcomes such as job stress as they do not possess the necessary life skills or experience to cope with it.…”
Section: Agementioning
confidence: 99%
See 3 more Smart Citations